There's something I can't seem to figure out.(adsbygoogle = window.adsbygoogle || []).push({});

say we have the function

f=xz +x'z'

why is this equals (x xor z)' ?

i thought using De-Morgan's law we shall get

(x xor z)'=(x'z+z'x)'=(xz'zx')=0

then why does (x xor z)'=xz+x'z' ?

and one more small thing,

say we have

(x xor y) xor (x xor z)'

why does (x xor y) xor (x xor z)' = (x xor y xor x xor z)'

how did they come to this term?

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# A smal problem with boolean algebra

**Physics Forums | Science Articles, Homework Help, Discussion**